2009
DOI: 10.1111/j.1365-2966.2009.15185.x
|View full text |Cite
|
Sign up to set email alerts
|

LSD: Lyman-break galaxies Stellar populations and Dynamics - I. Mass, metallicity and gas atz∼ 3.1

Abstract: We present the first results of a project, Lyman‐break galaxies Stellar populations and Dynamics (LSD), aimed at obtaining spatially resolved, near‐infrared (IR) spectroscopy of a complete sample of Lyman‐break galaxies at z∼ 3. Deep observations with adaptive optics resulted in the detection of the main optical lines, such as [O ii]λ3727, Hβ and [O iii]λ5007, which are used to study sizes, star formation rates (SFRs), morphologies, gas‐phase metallicities, gas fractions and effective yields. Optical, near‐IR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
473
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(535 citation statements)
references
References 116 publications
56
473
4
Order By: Relevance
“…Fig. 15 shows the result for GRB hosts with z > 4 compared to two other samples for field galaxies of z ∼ 2.3 (Erb et al, 2006) and z ∼ 3.1 (Mannucci et al, 2009). GRB 050904 at z = 6.29 with our corrected metallicity and GRB 060223A clearly lie below the galaxies at z ∼ 3.1 while the other four hosts, including GRB 100219A, are consistent with the relation at lower redshifts.…”
Section: The Mass-metallicity Relation At High Redshiftssupporting
confidence: 67%
See 2 more Smart Citations
“…Fig. 15 shows the result for GRB hosts with z > 4 compared to two other samples for field galaxies of z ∼ 2.3 (Erb et al, 2006) and z ∼ 3.1 (Mannucci et al, 2009). GRB 050904 at z = 6.29 with our corrected metallicity and GRB 060223A clearly lie below the galaxies at z ∼ 3.1 while the other four hosts, including GRB 100219A, are consistent with the relation at lower redshifts.…”
Section: The Mass-metallicity Relation At High Redshiftssupporting
confidence: 67%
“…It has become clear that the M-Z relation at increasing redshift changes towards lower metallicities for a given stellar mass (Kewley & Ellison, 2008;Savaglio et al, 2005;Erb et al, 2006;Mannucci et al, 2009). This effect is largely due to the enrichment with metals over time but the metal enrichment of galaxies is also a complex function of star-formation efficiency and feedback with the intergalactic medium.…”
Section: The Mass-metallicity Relation At High Redshiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schaye et al 2003;Fumagalli et al 2016b). Indeed, a ≈ 10%-solar metallicity resembles the metal content of the interstellar medium of ≈ 10 8.5 − 10 9 M galaxies according to the z ≈ 3 mass-metallicity relation (Mannucci et al 2009). In addition to tidal interactions, galactic outflows are also a plausible mechanism to enrich Figure 7.…”
Section: Contribution From In Situ Star Formationmentioning
confidence: 99%
“…The heavy element content of star-forming galaxies is characterized by a strong relation between the stellar mass and average gas-phase oxygen abundance (Lequeux et al 1979;Tremonti et al 2004). This so-called mass-metallicity relation (MZR) extends to low stellar mass galaxies (∼ 10 7 M⊙ Lee et al 2006;Zahid et al 2012a;Berg et al 2012) and is observed at intermediate (Savaglio et al 2005;Cowie & Barger 2008;Zahid et al 2011;Moustakas et al 2011;Zahid et al 2013a) and high redshifts (Erb et al 2006;Mannucci et al 2009;Laskar et al 2011). The metallicity at all stellar masses increases with time and the high mass end of the relation flattens at late times as galaxies enrich to an empirical upper limit in the gas-phase abundance (Zahid et al 2013a).…”
Section: Introductionmentioning
confidence: 99%